Dopo Soissons: Gli ultimi anni di Carlo il Semplice (923-929) - McNair, Fraser (Reti Medievali Rivista, 2017)
In August 923, Charles the Simple was imprisoned by Count Heribert II of Vermandois, spending the rest of his life in prison. The six years between his imprisonment and his death, however, have never been the focus of a sustained study: Charles usually disappears into a jail cell and out of history. This article uses the difficult source material for West Frankish history in the early and mid-920s to examine the resilience of Carolingian kingship,. To retain their position, this article argues, the regimes seeking to replace Charles had to navigate a confusing political environment in which there were no ready-made paths to consensus about what to do with an imprisoned king.